2013
DOI: 10.1371/journal.pone.0070909
|View full text |Cite|
|
Sign up to set email alerts
|

Specific Inhibition of the Redox Activity of Ape1/Ref-1 by E3330 Blocks Tnf-Α-Induced Activation of Il-8 Production in Liver Cancer Cell Lines

Abstract: APE1/Ref-1 is a main regulator of cellular response to oxidative stress via DNA-repair function and co-activating activity on the NF-κB transcription factor. APE1 is central in controlling the oxidative stress-based inflammatory processes through modulation of cytokines expression and its overexpression is responsible for the onset of chemoresistance in different tumors including hepatic cancer. We examined the functional role of APE1 overexpression during hepatic cell damage related to fatty acid accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…The chemotactic migration involves the horizontal and vertical migration and provides information about the single‐cell motility . Moreover, despite the fact that the conditions of the chemotaxis assay better mimic the in vivo tumour microenvironment, we cannot discard a possible binding of E3330 to the serum proteins contributing to a decrease in the amount of E3330 available to enter in the cells and interact with APE1, consequently decreasing the efficacy of protein redox function inhibition when compared to the wound‐healing assay. In view of this, some of the effects of E3330 herein observed could be even more evident if a lower concentration of serum was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemotactic migration involves the horizontal and vertical migration and provides information about the single‐cell motility . Moreover, despite the fact that the conditions of the chemotaxis assay better mimic the in vivo tumour microenvironment, we cannot discard a possible binding of E3330 to the serum proteins contributing to a decrease in the amount of E3330 available to enter in the cells and interact with APE1, consequently decreasing the efficacy of protein redox function inhibition when compared to the wound‐healing assay. In view of this, some of the effects of E3330 herein observed could be even more evident if a lower concentration of serum was used.…”
Section: Discussionmentioning
confidence: 99%
“…E3330 was found to suppress the inflammatory response of activated macrophages and to prevent the induction of inflammatory cytokines (IL‐8 and IL‐6) expression in hepatic cancer cell lines suggesting that this inhibitor can be used in inflammatory processes associated with tumours and liver pathologies. E3330 also inhibited the differentiation of adult human bone marrow‐derived mesenchymal stem cells (BM‐MSCs) and the growth of endothelial cell precursors and pancreatic cancer‐associated endothelial cells .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we also focus our attention on the immunohistochemical expression of APE1/ Ref-1 (APE1). This is involved both in the base excision repair (BER) pathway of DNA lesions, acting as the major apurinic/apyrimidinic (AP) endonuclease, and in transcriptional regulation of gene expression, where it functions as a redox co-activator of different transcription factors that could lead to increased interleukin (IL)-6 and IL-8 expression (Cesaratto et al 2013;Thakur et al 2015;Tell et al 2005). IL-6 and IL-8 are two important immune-modulatory cytokines that are part of the senescence-associated secretory phenotype (SASP) (Coppé et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…E3330 was also found to selectively inhibit growth/migration of human pancreatic cancer cells [8], suggesting that the APE1 redox function could represent a good candidate for inhibition of tumor invasion and metastasis. We recently demonstrated that E3330-treatment inhibits the TNFα-induced IL8 production driven by NF-κB, in hepatic cancer cell lines [9]. However, knowledge on the detailed molecular mechanisms responsible for the C65-mediated APE1 redox function and for the effects of E3330 inhibition on APE1 in vivo are only at its beginning.…”
Section: Introductionmentioning
confidence: 99%